2019
DOI: 10.3390/molecules24224086
|View full text |Cite
|
Sign up to set email alerts
|

Indigo Naturalis Ameliorates Dextran Sulfate Sodium-Induced Colitis in Mice by Modulating the Intestinal Microbiota Community

Abstract: Indigo naturalis (IN) is a traditional Chinese medicine, named Qing-Dai, which is extracted from indigo plants and has been used to treat patients with inflammatory bowel disease (IBD) in China and Japan. Though there are notable effects of IN on colitis, the mechanisms remain elusive. Regarding the significance of alterations of intestinal flora related to IBD and the poor water solubility of the blue IN powder, we predicted that the protective action of IN on colitis may occur through modifying gut microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 64 publications
3
32
0
Order By: Relevance
“…In a 3% DSS Kunming mouse model, IN significantly downregulated the expression of the pro-inflammatory cytokines IL-6, IL-8, and TNF-α, and upregulated the expression of the anti-inflammatory factor IL10. Combination 16 s rDNA sequence analysis showed that IN decreases the relative number of Turicibacter bacilli and increases the relative number of Peptococcus 64 . In RAW264.7 cells induced by LPS, IN inhibits the degradation of IκB-α, the production of TNF-α and IL-6, and the expression of COX-2 and iNOS 65 .…”
Section: Discussionmentioning
confidence: 99%
“…In a 3% DSS Kunming mouse model, IN significantly downregulated the expression of the pro-inflammatory cytokines IL-6, IL-8, and TNF-α, and upregulated the expression of the anti-inflammatory factor IL10. Combination 16 s rDNA sequence analysis showed that IN decreases the relative number of Turicibacter bacilli and increases the relative number of Peptococcus 64 . In RAW264.7 cells induced by LPS, IN inhibits the degradation of IκB-α, the production of TNF-α and IL-6, and the expression of COX-2 and iNOS 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Indirubin, a component of indigo naturalis, which is derived from the leaves and stems of indigo plants, is used in traditional Chinese medicine to treat inflammatory bowel disease [ 52 ]. A study of the molecular structure of indirubin indicates that it has a more three-dimensional structure compared to the more planar structure of the indigo molecule which is another component of indigo naturalis [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical treatment UC is usually treated with anti-in ammatory or immunosuppressive drugs that have the disadvantages of relapse after discontinuation, long-term adverse drug reactions, and unsatisfactory results in some refractory cases [18]. Other studies have proved that INN, IND and INB can improve UC, but their therapeutic mechanism is not clear [19][20][21].…”
Section: Discussionmentioning
confidence: 99%